MARKETING COMMUNICATION STRATEGY FOR ISLAMIC BOARDING SCHOOL-BASED EDUCATIONAL INSTITUTIONS - Shidiq , Muhammad; Saleha, Latifatus (Universitas Nurul Jadid, 2022)
Communication is an important component in education as a means to connect between educational components. The role of communication in education marketing is a positive interaction that must be built by stakeholders as an effort to maintain the existence of educational institutions. The importance of communication must be built internally in educational institutions and also externally in educational institutions in the form of the community as an effort to build institutional synergy with the community. This research uses descriptive qualitative analysis method . Data collection techniques were carried out through observation and interviews. While the data analysis technique uses Miles and Huberman. The results of the study show that the communication strategy used by Nuris Vocational School has not been successful in the New Student Admissions (PPDB) activities.